Marco de priorización de intervenciones en Agricultura Sostenible Adaptada al Clima (ASAC) - Corner-Dolloff, Caitlin; Nowak, Andreea C.; Lizarazo, Miguel (2015)
Presentation focusing on scaling up and measuring climate smart agriculture. Presented at a workshop on tools and methods for planning and decision-making for agriculture and climate change at COP20 in Lima, Peru.